2016
DOI: 10.1021/jacs.5b12259
|View full text |Cite
|
Sign up to set email alerts
|

KOtBu-Initiated Aryl C–H Iodination: A Powerful Tool for the Synthesis of High Electron Affinity Compounds

Abstract: An efficient iodination reaction of electron-deficient heterocycles is described. The reaction utilizes KO(t)Bu as an initiator and likely proceeds by a radical anion propagation mechanism. This new methodology is particularly effective for functionalization of building blocks for electron transport materials. Its utility is demonstrated with the synthesis of a new perylenediimide-thiazole non-fullerene acceptor capable of delivering a power conversion efficiency of 4.5% in a bulk-heterojunction organic solar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 33 publications
3
46
0
Order By: Relevance
“…The I ⋅⋅⋅ N contact in 2 b is closer (3.29 Å) and now has an in‐plane, near ideal XB at an angle of interaction at 177.8° that appears to weaken its neighboring square dimer interactions in the lattice (CB ave =3.78 Å, θ ave =99.5°, φ ave =0.0°, Φ ave =139.0°). Polarizing the iodine with the addition of a 5‐fluoro atom ( 3 a ) causes the I ⋅⋅⋅ N distance to shorten further to 3.11 Å, far below the van der Waals radii sum of 3.53 Å. The square interactions are suppressed, and a complementary CB‐type F ⋅⋅⋅ S contact exists at 2.97 Å with a N ‐S ⋅⋅⋅ F angle of 164.8° (F+S sum of van der Waals radii: 3.27 Å).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The I ⋅⋅⋅ N contact in 2 b is closer (3.29 Å) and now has an in‐plane, near ideal XB at an angle of interaction at 177.8° that appears to weaken its neighboring square dimer interactions in the lattice (CB ave =3.78 Å, θ ave =99.5°, φ ave =0.0°, Φ ave =139.0°). Polarizing the iodine with the addition of a 5‐fluoro atom ( 3 a ) causes the I ⋅⋅⋅ N distance to shorten further to 3.11 Å, far below the van der Waals radii sum of 3.53 Å. The square interactions are suppressed, and a complementary CB‐type F ⋅⋅⋅ S contact exists at 2.97 Å with a N ‐S ⋅⋅⋅ F angle of 164.8° (F+S sum of van der Waals radii: 3.27 Å).…”
Section: Resultsmentioning
confidence: 99%
“…The I···Nc ontact in 2b is closer (3.29 ) and now has an in-plane,n ear ideal XB at an angle of interaction at 177.88 that appears to weaken its neighboring square dimer interactions in the lattice (CB ave = 3.78 , q ave = 99.58, f ave = 0.08, F ave = 139.08). Polarizing the iodine with the addi-tion of a5 -fluoro atom (3a) [108] causes the I···Nd istance to shorten furthert o3 .11 ,f ar below the van der Waals radii sum of 3.53 .T he square interactions are suppressed, and a complementary CB-type F···Sc ontact exists at 2.97 with a N-S···Fa ngle of 164.88 (F + Ss um of van der Waals radii:3 .27 ). 5,6-Halogenation:W hile the parent scaffold 1b shows poorly aligned2 S-2N squares that become highly alignedi nt he 5,6difluorod erivative 5b (Figure 5), the squares cannotc ompete with heavierh alogens in this position.…”
Section: The 2s-2n Squarec Lass Assembled By Chalcogen Bondingmentioning
confidence: 99%
“…The UV–vis spectrum showed that this acceptor possessed a broad and strong absorption region between 300 and 600 nm, which was well complementary with the polymer donor PBDTT‐F‐TT that absorbed from 500 to 800 nm. After optimization, when blended with the PBDTT‐F‐TT donor, the T45 acceptor yielded the best PCE performance of 4.70% with the V oc , J sc , and FF value of 0.94 V, 9.74 mA cm −2 , and 0.49, respectively . Very recently, Wang group developed two novel nonfullerene small molecule acceptors T46 and T47, which the three perylene bisimide units or analogues surrounded by the phenyl cores.…”
Section: Nonfullerene Small Molecule Acceptorsmentioning
confidence: 99%
“…In a recent advance, potassium tert -butoxide was shown to promote efficient C–H silylation of heteroaromatic systems [ 34 , 35 , 36 ]. A similar potassium tert -butoxide radial initiation concept has also been applied to the C–H iodination of electron acceptor arenes ( Scheme 2 ) [ 37 ], which are typically resistant to electrophilic aromatic substitution and prone to reduction by organometallic reagents such as alkyl lithium and Grignard reagents that might be employed to deprotonate them. The new C–H iodination reaction proceeds at room temperature, and in many cases a sub-stoichiometric quantity of potassium tert -butoxide is sufficient to provide good reaction yields.…”
Section: Earth-abundant Metal-initiated Iodinationmentioning
confidence: 99%
“…Subsequent to this discovery of the tert -butoxide initiated C–H iodination, additional variations on the reaction conditions, including different initiators [ 38 ], and different halogen sources have been developed. The C–H iodination reaction has been utilized in the synthesis of the non-fullerene acceptor (TsCDI) 2 T ( Figure 2 ), which demonstrated promising properties as an electron transport material in an organic bulk heterojunction (BHJ) solar cell [ 37 , 39 ]. Subsequently, a direct C–H arylation of the parent PDI-thiazole has been developed enabling a modular synthesis of a number of (TsCDI) 2 analogues [ 39 ].…”
Section: Earth-abundant Metal-initiated Iodinationmentioning
confidence: 99%